The freshwater mussels (Bivalvia: Unionida) of Java: first island-wide assessment reveals new species, endemism, and urgent conservation needs - Alexandra, Zieritz; Ghivany Romadhoni, Sumaedi; Manuel, Lopes-Lima; Aswi A., Rofiqoh; Tabitha, Richmond; Jake, Dimon; Muhammad Azamuddeen, Mohammad Nasir; Hanna, Hartikainen; Khairul Adha, A. Rahim; Onrizal, Onrizal; Ivan N., Bolotov; Ristiyanti M., Marwoto (The Linnean Society of London, 2026)
The freshwater mussel (Bivalvia: Unionida) fauna of Java has never been examined comprehensively in a modern context, leading to a lack of a species inventory and knowledge on current species distributions and how these have been impacted by human activities over the past 70 years. In 2022/23, we surveyed 66 sites across 18 river basins of Java, and one site near the Rectidens sumatrensis type locality in Sumatra. Species were delineated and identified through an integrated morphological–molecular approach using COI-based phylogenetic and haplotype analyses. We found and sequenced 76 populations (= species-site occurrences) across 42 sites and 16 river basins, comprising eight native and one non-native species. Whilst confirming the presence of Lens contradens, Physunio superbus, Pilsbryoconcha exilis, Pseudodon vondembuschianus stat. rev., Rectidens orientalis comb. rev., and Sinanodonta pacifica (non-native), we provide the first records of Lens lugens, Pilsbryoconcha linguaeformis, and Pseudodon cokelatus sp. nov. Rectidens sumatrensis is absent from Java. Comparing our data to historical records indicates considerable population losses of most native species driven by the steep increase in urbanization, industrialization, mining, and other human activities. Conservation actions are urgently needed, particularly in the species-rich Bengawan Solo and Brantas River basins.